Academe vs. Hollywood: Sweet Liberty, or the Dilemmas of Historical Representation on Film - Spielmann, Guy (Lumen, 2021)
In Sweet Liberty, writer and director Alan Alda dramatizes the process of turning a scholarly study about the American Revolutionary War into a Hollywood film; he does so in ways that bring out the ethical complexities of adaptation, and eventually takes them to a meta-filmic level rarely seen in non-experimental cinema. While Sweet Liberty initially comes off as a light comedy with a predictable plot and ending, on closer inspection it compels us to reflect on the relationship between historical research and the popular entertainment industry. Although Alda appears to chastise the makers of period films who seek to capitalize on “history” without paying heed to historical facts, his professorial hero is not particularly critically minded either. Intentionally or not, Alda demonstrates that evaluating a mainstream history film cannot be reduced to a dichotomy between truth and fiction, and that research-based knowledge should also be viewed with a healthy skepticism.